Running out of bullets: The challenging management of acute hepatitis and SARS‐COV‐2 from the SMatteo COvid19 Registry (SMACORE). (6th August 2020) - Colaneri, Marta; Valsecchi, Pietro; Perotti, Luciano; Ludovisi, Serena; Seminari, Elena; Pieri, Teresa Chiara; Sacchi, Paolo; Bruno, Raffaele
Abstract: Liver impairment is frequent in patients with novel coronavirus disease (COVID‐19) and direct viral tropism for the liver has been proven. Since several of the currently administered drugs against severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) are possibly hepatotoxic, the management of patients with COVID‐19 and liver failure is still an almost unexplored field. Taking this challenging case of acute HBV with persistent hyperbilirubinemia and SARS‐COV‐2 infection with respiratory distress as a starting point, we here loop through this condition. Where the available therapeutic options are scarce, we here propose hemoperfusion (HP) as an attractive alternative to both delay any late‐stage progression of hyper inflammation process in COVID‐19 and remove the toxins involved in acute liver failure.